THE URGENCY OF MONITORING BITCOIN TRANSACTIONS IN PREVENTING MONEY LAUNDERING: A SADD AL-DZARI’AH PERSPECTIVE - Aulia Rahman Sitepu; Rahmat Hidayat (Journal Analytica Islamica, 2026)
The development of digital financial technology has driven the emergence of cryptocurrencies, particularly Bitcoin, as a transaction and investment instrument offering ease of cross-border transfers, decentralization, and a high degree of anonymity. However, these characteristics also open up significant opportunities for Bitcoin's misuse as a means of money laundering. In Indonesia, the dual policy of prohibiting the use of cryptocurrencies as a means of payment and recognizing them as a traded commodity creates legal uncertainty and weakens oversight. This study aims to analyze the urgency of monitoring Bitcoin transactions in preventing money laundering based on Indonesian positive law and the perspective of sadd al-dzari'ah. The study uses a normative juridical method with a legislative and conceptual approach. Data sources consist of primary, secondary, and tertiary legal materials analyzed qualitatively and descriptively. The results show that weak oversight, the absence of specific criminal sanctions, and the complex nature of crypto asset transactions provide opportunities for criminals to disguise the origins of illicit funds. From the perspective of sadd al-dzari'ah, this situation demands preventive measures to mitigate potential harm early on. Therefore, strengthening regulations, integrating anti-money laundering mechanisms, implementing the precautionary principle for crypto asset traders, and strengthening cooperation between national and international institutions are necessary. This study confirms that Bitcoin transaction oversight is an urgent need to ensure legal certainty, protect the public interest, and maintain the integrity of the national financial system.